INTEGRASI BALANCED SCORECARD DENGAN COSO ENTERPRISE RISK MANAGEMENT FRAMEWORK - Kurniawati Kurniawati (Universitas Bunda Mulia, 2017)
Companies in the 21st century face a complex business environment, full of opportunities, but pitted with the risks, in which they should make effective business decisions, improve interpersonal relations, meet societal obligations with the right strategy and manage risks. To overcome those challanges, the company needs management tools that can help the company to achieve its objective. Balanced Scorecard (BSC) dan COSO Enterprise Risk Management (ERM) Framework are management tools that are well-recognized and accepted among academicians and more importantly business leaders. They link the high level corporate strategies as determined by top level management with the day-to-day activities of the employees within the organization. Surprisingly, most of companies view BSC and COSO ERM as separate, unrelated management initiatives. In this article, we studies the feasibility of integrating BSC with the COSO ERM Framework, the framework for state-of-the art risk management, similiar to the way the BSC can be integrated with a variety of business management frameworks and methods. The integration of these two management tools (BSC and COSO ERM Framework) is a natural step in the evolution of corporate management.Keywords: Balanced Scorecard, COSO Enterprise Risk Management Framework, Strategic Management System, Risk Management, Key Performance Indicators, Key Risk Indicators.